Postpartum spontaneous bladder rupture - Zutshi, Vijay; Tiwari, Sana; Arora, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Spontaneous bladder rupture after normal vaginal delivery is a rare complication. Patients may present with abdominal distention, fever, haematuria, oliguria and deranged KFT (kidney function test). We are reporting two cases of primigravida with postpartum bladder rupture, one case was diagnosed at laparotomy and the other preoperatively. A patient who presents with retention of urine, haematuria ascites and deranged KFT after uneventful normal vaginal delivery, spontaneous bladder rupture should be suspected. Early diagnosis and management can decrease the morbidity.